Physiological and functional aspects of metal-binding protein associated with mercury in the liver tissue of pirarucu (Arapaima gigas) from the Brazilian Amazon - Cunha Bataglioli, Izabela da [UNESP]; Souza Vieira, José Cavalcante [UNESP]; Vitor de Queiroz, João [UNESP]; da Silva Fernandes, Mileni; Bittarello, Alis Correia [UNESP]; Braga, Camila Pereira; Rabelo Buzalaf, Marília Afonso; Adamec, Jiri; Zara, Luiz Fabrício; Magalhães Padilha, Pedro de [UNESP] (Elsevier, 2019)
High concentrations of mercury found in soils, sediments, fish, and humans of the Amazon region have gained prominence in scientific studies during the last decade. However, studies related to the elucidation of mercury toxicity mechanisms in ichthyofauna at the molecular and metallomic levels that seek to elucidate physiological and functional aspects, as well as the search for biomarkers of mercury exposure, are still sparse. In the search for these answers, the present study analyzed the hepatic tissue proteome of the Arapaima gigas (pirarucu) fish species collected in the Jirau hydroelectric power plant reservoir in the state of Rondônia state, Brazil, in order to identify mercury-related metal-binding proteins and to elucidate their physiological and functional aspects. The proteomic profile of the hepatic tissue of Arapaima gigas was obtained by two-dimensional electrophoresis (2D-PAGE) and the presence of mercury was mapped in the protein SPOTS by graphite furnace atomic absorption spectrometry(GFAAS). Mercury was detected in 18 protein SPOTS with concentrations ranging from 0.13 ± 0.003 to 131.00 ± 3 mg kg−1. The characterization of the protein SPOTS associated with mercury was performed by electrospray ionisation tandem mass spectrometry (ESI–MS/MS), and 10 proteins were identified. Bioinformatics analyses showed that most of the proteins found linked to mercury were involved in cellular component processes and biological processes. For the most part, protein sequences have cellular functions comprising catalytic, binding, sense of localization, and metabolic processes.
Keywords: 2D-PAGE; Bioinformatics analysis; ESI-MS/MS; Mercury in fish; Metal-binding protein; Metalloprotein